Inflation-dependent exchange rate pass-through in Sweden: Insights from a logistic smooth transition VAR model - Gabriella Linderoth; Malte Meuller (Sveriges Riksbank, 2024)
This paper provides novel estimations of a non-linear exchange rate pass-through dependent on inflation for Sweden using a logistic smooth transition vector autoregressive model. The model enables smooth transitions between high and low inflation regimes, mirroring the dynamics of the economy and capturing regime-specific effects. The results show that the pass-through from an exchange rate depreciation shock to consumer prices depends on the level of inflation, reaching 17.4% in the high inflation regime and 6.9% in the low inflation regime. The estimations utilize data from the period 1995Q1 to 2023Q2, covering periods of both low and high inflation, as well as substantial exchange rate depreciations. The pass-through is also estimated for producer and import prices, establishing a decreasing pass-through along the pricing chain. We find limited evidence of a regimedependent pass-through to producer prices and no evidence for import prices. The findings suggest stronger monetary policy reactions following a depreciation of the exchange rate in high-inflation environments to limit the pass-through and, by extension, the impact on consumer prices.
Keywords: C32; E31; E52; 330; Exchange Rate Pass-Through; Sweden; Inflation; Non-Linear; Logistic Smooth Transition Vector Autoregressive